Hindu Religious Life Reflected By Kiranagama - Padmanaban, S. (My University, 2015)
Sivagamas orated by Siva There are divided by two and Moolagama , upagama.Moola sivagagama twenty eight and upagamas two hundred and seven Mool sivagamas oveted by siva’s five faces, there are isana, tatpurusha, agora, vamadeva and satyojathe Sivagama’s tantarapatala says crieted tradition and oveted tradition of sivagamas Kiranagamas is one of moola sivagamas Kiranagamas discribets one of the contents pointed out hindu religion life this tradition describes about the value of hindu religion life and the tradition from Kiranagama this research perpous as above by discribtional research the perpous of this research to know about the several points of hindu religious life this research person pointed the hindu religious life philosophical reflection from Kiranagama
Keywords: Sivagama; Kiranagama; Saivasiddhantam; Pati; Pasu; Pasa; Maya; Kanma